2002
DOI: 10.1055/s-2002-19887
|View full text |Cite
|
Sign up to set email alerts
|

Pedicled Foot Fillet Flap Based on the Tibialis Anterior Vessels: Case Report

Abstract: A case of an 18-year-old male with extensive posterior and lateral soft-tissue loss of the lower leg is reported. There was a segmental defect of 20 cm in the tibialis posterior neurovascular bundle, and the injury was not considered reconstructable. There was extensive soft-tissue trauma to the posterior compartments of the leg, with an intact and well-perfused foot. A primary amputation was indicated. The foot was used as a fillet flap for tibial length preservation and optimal stump coverage. The foot fille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The free flap is harvested from the ipsilateral amputated part to cover the below knee or above knee amputation stump. Cavadas et al, 9 Chiang et al, 3 Johandi et al, 10 Ghali et al, 11 Russell et al, the amputated leg to fill the defects in the amputation stump and hand. Chiang et al 3 reported S3 sensory recovery in two patients at 40 months and 4 years follow-up and normal sensation at the center of the transferred flap in one patient at 1 year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The free flap is harvested from the ipsilateral amputated part to cover the below knee or above knee amputation stump. Cavadas et al, 9 Chiang et al, 3 Johandi et al, 10 Ghali et al, 11 Russell et al, the amputated leg to fill the defects in the amputation stump and hand. Chiang et al 3 reported S3 sensory recovery in two patients at 40 months and 4 years follow-up and normal sensation at the center of the transferred flap in one patient at 1 year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The free flap is harvested from the ipsilateral amputated part to cover the below knee or above knee amputation stump. Cavadas et al, 9 Chiang et al, 3 Johandi et al, 10 Ghali et al, 11 Russell et al, 2 and Gumley et al 8 have reported the successful usage of foot fillet free flaps as pedicled or free flap to cover a posttraumatic lower limb amputation stump. Pribaz et al 12 utilized the free flaps and great toe harvested from the amputated leg to fill the defects in the amputation stump and hand.…”
Section: Discussionmentioning
confidence: 99%
“…The foot fillet flap, pedicled on the tibialis anterior vessels, preserving the deep plantar, first dorsal metatarsal and anterior communicating vessels, can be used for successful prosthetic adaptation (8). Every attempt should be made to preserve an adequate stump length, particularly in young patients, to enable the proper fitting of the prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Amputated sole of the foot has been used as a fillet flap to preserve tibial length and optimal stump coverage during primary amputation in a young adult. The foot fillet flap, pedicled on the tibialis anterior vessels, preserving the deep plantar, first dorsal metatarsal and anterior communicating vessels, can be used for successful prosthetic adaptation (8). Every attempt should be made to preserve an adequate stump length, particularly in young patients, to enable the proper fitting of the prosthesis.…”
Section: Discussionmentioning
confidence: 99%